NUMERICAL TOOLS AND ARTIFICIAL INTELLIGENCE IN MEDICAL RESEARCH - DUGUET, Anne-Marie (MEDECINE LEGALE DROIT MEDICAL, 2025)
Digital tools have developed in all fields, particularly in health and medical research. Without being exhaustive, this presentation wishes to shed light, based on a few examples of projects, on how medical research is progressing thanks to digital tools, data science and applications of algorithms and artificial intelligence. Artificial intelligence is considered here as a set of activities performed by machines. We deliberately dismiss the possibilities offered by Artificial Intelligence in the field of prediction. This article first presents the progress generated by numerical tools in medical research and research on numerical tools for health. In a second step, the legal framework and ethical aspects are discussed.